Oxford Research Encyclopedia of Communication 2019
DOI: 10.1093/acrefore/9780190228613.013.805
|View full text |Cite
|
Sign up to set email alerts
|

Employment Conditions in Journalism

Abstract: Amid the rise of atypical and casual employment across economic sectors and the decline in profits taking place in media organizations internationally, the conditions under which journalists work are changing and, for many, worsening. The number of employed journalists has declined significantly since the late 20th century, and the real salaries of the remaining journalists have decreased or remained mostly stagnant. Female journalists, freelancers, and online journalists are paid (often significantly) less th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 0 publications
1
13
0
2
Order By: Relevance
“…Studies on changes in the labor market have often concluded that externalizing news production transfers organizational risks over to the freelancer (see Norbäck & Styhre, 2019), freelance and entrepreneurial journalists experience intense income insecurity (Gollmitzer, 2019), and changed working conditions lead to overall precarity that prohibits journalism's institutional functioning (Hayes & Silke, 2019). The issue of freelancers' work conditions, financial vulnerability, and various rights restrictions is not new in journalism studies (see Baines & Kennedy, 2010).…”
Section: Employment Regimes and Precaritymentioning
confidence: 99%
See 1 more Smart Citation
“…Studies on changes in the labor market have often concluded that externalizing news production transfers organizational risks over to the freelancer (see Norbäck & Styhre, 2019), freelance and entrepreneurial journalists experience intense income insecurity (Gollmitzer, 2019), and changed working conditions lead to overall precarity that prohibits journalism's institutional functioning (Hayes & Silke, 2019). The issue of freelancers' work conditions, financial vulnerability, and various rights restrictions is not new in journalism studies (see Baines & Kennedy, 2010).…”
Section: Employment Regimes and Precaritymentioning
confidence: 99%
“…The definition of freelance journalists has diverged for many reasons (Briggs, 2012;Deuze, 2009;Deuze & Witschge, 2018). On the one hand, news organizations have increasingly outsourced content production due to decreasing revenues and changing labor markets (Edstrom & Ladendorf, 2012;Gollmitzer, 2019;Rosenkranz, 2019). On the other hand, to meet the demand for novel and divergent skills news organizations use non-journalistic actors (e.g., fact-checkers initiatives, data activists, start-up specialists, etc.)…”
Section: Introductionmentioning
confidence: 99%
“…I flere land er det en økende andel av journalister som jobber utenfor de tradisjonelle redaksjonene (Deuze & Witschge 2018;Gollmitzer 2020). I Norge er andelen mediefrilansere lavere enn i andre europeiske land.…”
Section: Innledningunclassified
“…Også tidligere arbeidsmiljøundersøkelser i mediene viser at andelen deltidsfrilansere er høy (Gollmitzer 2020;Sørensen mfl. 2005: 225).…”
Section: Avmakt -Marginalisering Og Deprofesjonaliseringunclassified
“…In the pure market logic of newspaper owners and publishers, it makes good business sense. Yet, to rank-and-file newsworkers, it looks and feels a lot like their employer does not much value them as the fulcrum of the news enterprise (e.g., Edge, 2014; Gollmitzer, 2019; Roberts, 1997). Market logic, in this sense, sees newsworkers as exploitable and expendable in the pursuit of profit.…”
mentioning
confidence: 99%